Eficácia da limpeza manual versus automatizada para a remoção de Staphylococcus epidermidis aderido à superfície de instrumental cirúrgico em diferentes intervalos por contaminação experimental - Síntia de Souza Evangelista (2019)
Surgical instruments are subjected to successive contamination and processing cycles throughout their useful life. The presence of areas of difficult access, such as serration and rack, as well as the adoption of improper practices during pre-cleaning and cleaning, can make it difficult to remove residues after each use, favoring the formation of biofilm. Widely isolated as contaminants of surgical instruments after use, Staphylococcus epidermidis are recognized for their ability to form biofilm on different surfaces. In this sense, the question is: how the manual and automated cleaning methods perform on the removal of S. epidermidis adhered to the surface of surgical instruments submitted to experimental contamination for different intervals? We aimed at comparing two leaning protocols, manual and automated, regarding their capacity for removing S. epidermidis from the surface of surgical instruments submitted to different intervals of contamination. This was an experimental research conducted at the Oral and Anaerobic Microbiology Laboratory, ICB/UFMG and at the UFMG microscopy center. Straight crile tweezers were selected to analyze areas with different challenges to the cleaning process: uneven (serrated and rack) and smooth (rod) surface. The specimens were contaminated by immersion in Triptical Soya Broth (TSB), containing 106 CFU/mL of a clinical sample of S. epidermidis. The bacterial adherence and the removal capacity of these microorganisms, submitted to manual or automated cleaning, were verified after one, two, four, six, eight, and 12 hours. Results were evaluated by microbiological culture and scanning electron microscopy (SEM). The results were analyzed using descriptive statistics and analysis of variance (ANOVA) techniques at a level of 5% confidence. In the group subjected to contamination, the bacterial load increased over time, ranging from 101–102 CFU/cm2 after one hour to 104 CFU/cm2 within 12 hours. Bacterial adhesion was observed after one hour, with the formation of biofilm after two hours, and, in general, an increase in the concentration of microorganisms at subsequent times. The microbial load was reduced by 1-2 log10 after manual cleaning and between 1-3 log10 after automated cleaning and was considered significant (p<0.05) in all fragments and times evaluated in the last group. SEM analysis showed the permanence of biofilm after using both methods. In general, rod fragments presented lower microbial load during the evaluation period in the different groups evaluated, and this difference (p<0.05) was significant at six hours. In conclusion, the S. epidermidis presented fast adherence capacity and biofilm formation after two hours of contact with the surgical instruments with bacterial load of 102 CFU/cm2. The automated cleaning was more effective than manual cleaning. However, neither method completely removed the biofilm formed. Pre-cleaning conditions, as well as the presence of difficult access areas, such as serration and rack, are critical factors in the processing quality of surgical instruments.